Endoscopic management of enteral tubes in adult patients – Part 1: Definitions and indications. European Society of Gastrointestinal Endoscopy (ESGE) Guideline - Arvanitakis, Marianna; Gkolfakis, Paraskevas; Despott, Edward J.; Ballarin, Asuncion; Beyna, Torsten; Boeykens, Kurt; Elbe, Peter; Gisbertz, Ingrid; Hoyois, Alice; Mosteanu, Ofelia; Sanders, David S.; Schmidt, Peter T.; Schneider, Stéphane M.; van Hooft, Jeanin E. (Endoscopy, 2020)
ESGE recommends considering the following indications for enteral tube insertion: (i) clinical conditions that make oral intake impossible (neurological conditions, obstructive causes); (ii) acute and/or chronic diseases that result in a catabolic state where oral intake becomes insufficient; and (iii) chronic small-bowel obstruction requiring a decompression gastrostomy.Strong recommendation, low quality evidence.ESGE recommends the use of temporary feeding tubes placed through a natural orifice (either nostril) in patients expected to require enteral nutrition (EN) for less than 4 weeks. If it is anticipated that EN will be required for more than 4 weeks, percutaneous access should be considered, depending on the clinical setting.Strong recommendation, low quality evidence.ESGE recommends the gastric route as the primary option in patients in need of EN support. Only in patients with altered/unfavorable gastric anatomy (e. g. after previous surgery), impaired gastric emptying, intolerance to gastric feeding, or with a high risk of aspiration, should the jejunal route be chosen.Strong recommendation, moderate quality evidence.ESGE suggests that recent gastrointestinal (GI) bleeding due to peptic ulcer disease with risk of rebleeding should be considered to be a relative contraindication to percutaneous enteral access procedures, as should hemodynamic or respiratory instability.Weak recommendation, low quality evidence.ESGE suggests that the presence of ascites and ventriculoperitoneal shunts should be considered to be additional risk factors for infection and, therefore, further preventive precautions must be taken in these cases.Weak recommendation, low quality evidence.ESGE recommends that percutaneous tube placement (percutaneous endoscopic gastrostomy [PEG], percutaneous endoscopic gastrostomy with jejunal extension [PEG-J], or direct percutaneous endoscopic jejunostomy [D-PEJ]) should be considered to be a procedure with high hemorrhagic risk, and that in order to reduce this risk, specific guidelines for antiplatelet or anticoagulant use should be followed strictly.Strong recommendation, low quality evidence.ESGE recommends refraining from PEG placement in patients with advanced dementia.Strong recommendation, low quality evidence.ESGE recommends refraining from PEG placement in patients with a life expectancy shorter than 30 days.Strong recommendation, low quality evidence*.